2021
DOI: 10.1016/j.jtcme.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Altered presence of extra cellular matrix components in murine skin cancer: Modulation by Azadirachta indica leaf extract

Abstract: Background and aim Although, the anticancer potential of Aqueous Azadirachta indica leaf extract (AAILE) has been robustly established against cutaneous squamous cell carcinoma (SCC) in mice, however, its ability in modulating tumor associated extra cellular matrix (ECM) is largely unknown. Therefore, the present study was conceived to explore changes in ECM during murine skin cancer and its chemoprevention by AAILE. Experimental procedure Ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Adverse ECM accumulation in glomerulus and tubulointerstitium promotes renal fibrosis and subsequent deterioration of renal function 2 . ECM regulation by neem-derived compounds has already been shown in cancer studies 33,34 . Therefore, in our current study, we examined the effect of Nimbidiol on the expression of important ECM proteins such as collagen IV (Col IV), fibronectin, and elastin in the diabetic kidney.…”
Section: Nimbidiol Ameliorated Resistive Index (Ri) Of the Renal Cort...mentioning
confidence: 82%
See 1 more Smart Citation
“…Adverse ECM accumulation in glomerulus and tubulointerstitium promotes renal fibrosis and subsequent deterioration of renal function 2 . ECM regulation by neem-derived compounds has already been shown in cancer studies 33,34 . Therefore, in our current study, we examined the effect of Nimbidiol on the expression of important ECM proteins such as collagen IV (Col IV), fibronectin, and elastin in the diabetic kidney.…”
Section: Nimbidiol Ameliorated Resistive Index (Ri) Of the Renal Cort...mentioning
confidence: 82%
“…A wide range of neem extracts and neem-derived compounds have also been reported to show antihyperglycemic activity 29 . Moreover, earlier studies have also suggested that bioactive compounds from A. indica regulate ECM proteins by modulating expression of MMPs in different diseases including wide-spectrum cancer studies [30][31][32][33][34] . Recently, therapeutic intervention of neem extract has been shown to abrogate inflammation-driven renal fibrosis by reducing ECM accumulation in UUO nephropathy 35 .…”
mentioning
confidence: 99%
“…Chugh et al (2018) observed that AAILE treatment caused a marked reduction in skin papilloma formation as unveiled via scrutinizing the cell proliferation, cell count, DNA/amide ratio, ODC, ATM, and LDH within skin/papilloma of mice. After that, Chugh and Koul (2021) observed that AAILE treatment decreased the GAGs levels, collagen levels, and CEA levels, and thus modulated the ECM to reduce the metastasis of skin carcinoma in the DMBA/TPA-induced murine skin cancer model. Table 1 lists a few findings validating its protective role against NMSC.…”
Section: A Indica (Neem)mentioning
confidence: 96%